Gene duplication, conservation, and divergence of activating transcription factor 5 gene in zebrafish. Issue 5 (28th February 2022) - Zhu, Huihui; Zhang, Xiaoyi; Xu, Shifan; Wu, Jiawen; Hou, Mengying; Zhao, Haobin; Zhou, Qingchun; Zhong, Xueping
Abstract: Activating transcription factor 5 (Atf5) is a member of the ATF/CREB family of transcription factors and involved in diverse cellular functions and diseases in mammals. However, the function of atf5 remains largely unknown in fish. Here, we report the expression pattern and function of duplicated atf5 genes in zebrafish. The results showed that the gene structures of zebrafish atf5a and atf5b were similar to their mammalian orthologs. Zebrafish Atf5a and Atf5b shared an amino acid sequence identity of 40.7%. Zebrafish atf5a and atf5b had maternal origin with dynamic expression during embryonic development. Zebrafish atf5a mRNA is mainly enriched in olfactory epithelium, midbrain, and hindbrain, while zebrafish atf5b mRNA is mainly detected in midbrain, hindbrain, and liver during embryogenesis. The results of acute hypoxia experiment showed that atf5a mRNA was significantly upregulated in the brain, liver, and muscle, while atf5b mRNA was just increased significantly in the brain. Functional analysis showed that knockdown of atf5a affects the development of the ciliated neurons in zebrafish embryos. The effect was enhanced when atf5a MO was co‐injected with atf5b MO. The development of ciliated neurons in zebrafish embryos was not affected by injection of atf5b MO alone. atf5a knockdown also affects the development of early‐born olfactory neurons. The effects caused by atf5a knockdown could be rescued by atf5b mRNA. These results suggest that the duplicated atf5 genes may have evolved divergently and play redundant biological roles in the development of olfactory sensory neurons in zebrafish. Abstract : The expression patterns of zebrafish atf5a and atf5b are different but overlap in some regions during embryogenesis. Knockdown of atf5a affected the development of the ciliated neurons in zebrafish embryos. The development of ciliated neurons in zebrafish embryos was not affected by injection of atf5b MO. The effects caused by atf5a knockdown could be rescued by atf5a mRNA and atf5b mRNA. Zebrafish atf5a and atf5b genes may have evolved divergently and play redundant biological roles in olfactory sensory neurons development. Research Highlights: The expression patterns of zebrafish atf5a and atf5b are different but overlap in some regions during embryogenesis and in adult tissues. Zebrafish atf5a and atf5b genes may have evolved divergently and play redundant biological roles in olfactory sensory neurons development.